Flood Susceptibility Mapping in Gending District by Comparison Frequency Ratio and Weight of Evidence for Mitigation Strategy - Bachtiar Ilham Maulana; Entin Hidayah; Gusfan Halik (Kadiri University, 2023)
Floods are natural disasters that occur all over the world. Gending District in Probolinggo Regency, East Java, is an area that often experiences floods and causes various losses. A flood susceptibility map needed to prepare appropriate mitigation actions. Choosing the right method will produce a more accurate flood susceptibility map. The research aims to make a flood susceptibility map in Gending District by comparing the Frequency Ratio (FR) and Weight of Evidence (WofE) methods and providing appropriate mitigation recommendations. Six data factors that cause flooding are used: slope, elevation, land use, normalized difference vegetation index (NDVI), curvature, and rainfall. The data obtained were processed using the FR and WofE methods, which were then validated using the Receiver Operating Characteristics (ROC) method. The validation value is calculated using the ROC chart's Area Under Curve (AUC). The higher the AUC value, the better. The study's results revealed that the correct method for making a flood susceptibility map in Gending District was FR with an AUC value of 92.8%, while the WofE method was 90.4%. The flood susceptibility map illustrates that 14% of the area is in very high and high flood-prone zones, 23% is in the moderate zone, and 63% is in the safe zone. The appropriate mitigation strategy based on the highest FR value is creating drainage networks, and green open spaces, normalizing rivers in residential areas, and implementing selective logging and reforestation programs. The results of this study are used to reduce the impact and risk of future flood disasters.